PERBANDINGAN ANALISIS STRUKTURAL CERITA RAKYAT “LEGENDA MATAHARI DAN PEMANAH ULUNG” ASAL JAMBI DAN CERITA PENDEK “HOUI DAN CHANA” ASAL JEPANG - Firdaus, Muhamad Yuda; Hartati, Dian (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2022)
The research was conducted to see two literary works from different countries, languages, and cultures but have similarities and differences in them. The creation of literary works cannot be separated from the culture of society. The source of the research data is the Jambi Indonesian folklore “The Legend of the Sun and the Ultimate Archer” with the short story “Houi dan Chana” by Siahara Akemi. The research uses a qualitative research paradigm. The findings show that the similarities between the two literary works can be seen in the storyline, which has a forward plot and language style using language that is easy to understand and there is a personification style. The differences are in the theme, characters and characterizations, setting, point of view, and mandate. The folklore has the theme of regret from a cruel king, while the short story has the theme of kindness being repaid by cruelty. There are four characters in folklore while in short stories there are five characters. In folklore the setting is in the clouds and at night, while in the short story the setting is in heaven, the house, and the mountain and the setting is nearing night. The point of view in folklore uses a third-person omniscient point of view, while in short stories it uses a mixed point of view. The mandate in folklore is that as a king, don't be cruel, and repent by not committing cruel acts anymore is the best way to atone for sins that have been committed. While in the short story, it is still doing good even though getting a bad reply.Keywords: Structural analysis, comparative analysis, folklore, short story